The Impact Of Announcements Of Mergers And Acquisitions (M&A) On Stock Returns - Sampurna, Dian Surya; Alexandri, Benny; Pragiwani, Meita; Suhardi, Yusuf; Ikaputri, Marcelina Wahyuningtyas (Universitas Dharma Wacana, 2024)
One of the corporate actions carried out by companies is mergers and acquisitions (M&A). This research aims to examine the impact of merger and acquisition (M&A) announcements on stock returns of banking companies listed on LQ 45 for the 2011-2021 period. This research uses the event study method, with 3 banking companies from 8 merger and acquisition (M&A) events, with an event window of 91 days, namely 45 days pre-announcement, 1 day of announcement and 45 days post-announcement. The results of this research show that the market responded positively to 8 merger and acquisition (M&A) announcement events. The benefit of this research is for policy makers to stimulate stock prices with the help of various announcements from their corporate action strategies. Investors will be helped in understanding stock market mechanisms in making wise investment decisions before reacting to corporate actions. Meanwhile, policy makers are interested in influencing stock prices and investors are interested in the composition of risk-return parameters in their portfolios. This research will act as an important investment tool for both.